2012
DOI: 10.1093/eurheartj/ehs034
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of coronary vessel dominance in relation to significant coronary artery disease determined with non-invasive computed tomography coronary angiography

Abstract: The presence of a left dominant system was identified as an independent predictor of non-fatal myocardial infarction and all-cause mortality, especially in patients with significant CAD on CTA. Therefore, the assessment of coronary vessel dominance on CTA may further enhance risk stratification beyond the assessment of significant CAD on CTA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 24 publications
1
52
0
2
Order By: Relevance
“…A coronary artery system was classified as right dominant when the PDA originated from the right coronary artery (RCA), while left dominance was defined when the PDA originated from the left circumflex artery (LCX). A balanced dominant coronary system was categorised when the PDA rose from the RCA in combination with a large posterolateral branch originating from the LCX reaching near the posterior interventricular groove 2 . Right and balanced were referred to as non-left dominance.…”
Section: Angiographic Assessment Of Coronary Artery Dominancementioning
confidence: 99%
See 2 more Smart Citations
“…A coronary artery system was classified as right dominant when the PDA originated from the right coronary artery (RCA), while left dominance was defined when the PDA originated from the left circumflex artery (LCX). A balanced dominant coronary system was categorised when the PDA rose from the RCA in combination with a large posterolateral branch originating from the LCX reaching near the posterior interventricular groove 2 . Right and balanced were referred to as non-left dominance.…”
Section: Angiographic Assessment Of Coronary Artery Dominancementioning
confidence: 99%
“…A few registries and studies have shown relations between left dominance and inferior clinical outcome [2][3][4] , but the patient populations of these studies differed significantly from that of the TWENTE trial 5 .…”
Section: Clinical Outcomementioning
confidence: 99%
See 1 more Smart Citation
“…Most of the time a PL is supplied by LCX and PDA by RCA. 2 There are studies showing peri-procedural myocardial infarction and adverse outcomes in those patients who have left dominance. [2][3][4] The studies mainly assessed procedural outcomes in patients undergoing percutaneous coronary interventions (PCI).…”
Section: Introductionmentioning
confidence: 99%
“…2 There are studies showing peri-procedural myocardial infarction and adverse outcomes in those patients who have left dominance. [2][3][4] The studies mainly assessed procedural outcomes in patients undergoing percutaneous coronary interventions (PCI). There is limited knowledge about the relation between coronary dominance patterns and the risk of various adverse clinical events that can occur following coronary angiography in Nepal.…”
Section: Introductionmentioning
confidence: 99%